Penerapan Metode Statistical Process Control terhadap Kualitas Benang 40 CD KNB Pada Proses Warping di Perusahaan PC GKBI - Dzul Arnendy Muhammad; Yunita Primasanti; Erna Indriastiningsih (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
In the textile industry, quality control is a crucial aspect to ensure the stability and consistency of production results. One of the important stages in yarn production is the warping process, which has a significant influence on the quality in the subsequent process. This study aims to apply the Statistical Process Control (SPC) method to assess the quality of 40 CD KNB yarn in the warping process in the GKBI PC company, Preparation Department, and determine whether the process is already in a controlled condition. Currently, the average quality and amount of monthly yarn production show fluctuations with a downward trend of 1.64 per 5,000,000 meters in the period February–July 2024. This figure is below the company's daily production target of 1.00 per 5,000,000 meters, so the target has not been achieved. This discrepancy indicates the need for a more systematic evaluation and improvement of the quality control system. Based on the analysis of the X-Bar control chart in January 2025, two data points were found outside the control limits (UCL = 176.8; LCL = -29.5; average = 73.6), ie on January 4 and 20. The main cause of such uncontrollability is the weak yarn that comes from the rewinding process. Check sheet analysis and Pareto diagram shows that the most common factors causing thread breakage are weak threads. Furthermore, through the cause-and-effect diagram (fishbone diagram), it was identified that the factors that cause thread breakage come from four categories: human (HR), material (raw material), environment, and machine. Of the four factors, human resources and material aspects are the biggest contributors to influence. Therefore, it is recommended that quality control at PC GKBI be strengthened through training and counseling programs to employees, in order to improve skills and awareness of the importance of quality. This step is expected to reduce the rate of yarn breakage, maintain the stability of the production process, and ensure consistent achievement of company targets.